2018
DOI: 10.1101/gr.232645.117
|View full text |Cite
|
Sign up to set email alerts
|

Human long intrinsically disordered protein regions are frequent targets of positive selection

Abstract: Intrinsically disordered regions occur frequently in proteins and are characterized by a lack of a well-defined three-dimensional structure. Although these regions do not show a higher order of structural organization, they are known to be functionally important. Disordered regions are rapidly evolving, largely attributed to relaxed purifying selection and an increased role of genetic drift. It has also been suggested that positive selection might contribute to their rapid diversification. However, for our own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 71 publications
(70 reference statements)
6
64
0
Order By: Relevance
“…Accumulating evidence suggests that relaxed structural constraints provide an advantage when accommodating multiple overlapping functions in coding regions (collectively referred to as synonymous constraint elements) (Castillo et al, 2014;Pancsa and Tompa, 2016). Additionally, recent studies have found a higher degree of positive selection on proteins with intrinsically disordered regions (Nillson et al, 2011;Afanasyeva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that relaxed structural constraints provide an advantage when accommodating multiple overlapping functions in coding regions (collectively referred to as synonymous constraint elements) (Castillo et al, 2014;Pancsa and Tompa, 2016). Additionally, recent studies have found a higher degree of positive selection on proteins with intrinsically disordered regions (Nillson et al, 2011;Afanasyeva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus terminal regions were considered as "evolutionary playgrounds" for the innovation of new functions [36]. This reduced efficacy of selection at the protein terminus, especially in eukaryotes because of their lower effective population size compared to prokaryotes [37] may have provided the permissive environment for the fixation of disordered promoting amino acids which are generally associated with high rates of insertions, deletions and substitutions [7,8,10]. It is possible that disordered residues in these regions tend to be less deleterious in eukaryotes than in prokaryotes facilitating their fixation.…”
Section: Discussionmentioning
confidence: 99%
“…We used genomes of 57 bird species with high quality annotations from NCBI RefSeq (O'Leary et al (Table S2). First, 12,013 orthologous protein coding genes were retrieved using RefSeq and HGNC gene identifiers, alongside reciprocal BLAST approaches based on three focal species, chicken, great tit and zebra finch -three of the best annotated high quality bird genomes available to date (Li et al 2003;Östlund et al 2009;Afanasyeva et al 2018). We then performed a first set of alignment runs using PRANK (Löytynoja and Goldman 2008).…”
Section: Multiple Sequence Alignments For Protein Coding Genesmentioning
confidence: 99%